Population-Based Stroke Survey in Mumbai, India: Incidence and 28-Day Case Fatality - Dalal, P.M.; Malik, S.; Bhattacharjee, M.; Trivedi, N.D.; Vairale, J.; Bhat, P.; Deshmukh, S.; Khandelwal, K.; Mathur, V.D. (Neuroepidemiology, 2008)
Objectives: The aims of this study were (1) to establish a prospective community-based stroke registry in Mumbai of subjects having ‘first-ever stroke’ (FES) and (2) to collect standardized data on annual incidence, stroke subtypes, and case fatality rate at 28 days during the years 2005 and 2006. Background: An estimated 5.8 million people died from stroke (cerebrovascular disease) in 2005, two thirds of them were from low-/middle-income countries but reliable population-based studies are scarce. Methods: The manual on WHO STEPwise approach to stroke surveillance (STEPS Stroke; http://www.who.int/chp/steps/Manual pdf) was the operational protocol. We selected a well-defined community (H-district) having verifiable census data and being representative of the population structure of Mumbai (Bombay). Of 337,391 permanent residents, 156,861 persons between the age of 25 and 94+ years who were eligible for survey were screened. The responses to a predefined questionnaire (version 2.0) were entered in coded data sheets for analysis. Results: During the 2-year study period (January 2005 to December 2006), 456 (238 males and 218 females) had FES, indicating an annual incidence in subjects of 25 years and above of 145/100,000 persons (CI 95%: 120–170); for males it is 149/100,000 persons (CI 95%: 120–170) and for females it is 141/100,000 persons (CI 95%: 120–160). The age-standardized rate for study population (both sexes) by the direct method using Segi’s 1996 world population is 152/100,000/year (CI 95%: 132–172). Stroke diagnosis was supported by computed tomography in 407 (89.2%) of 456 FES cases: 366 (80.2%) had ischemic stroke, 81 (17.7%) had hemorrhagic stroke and 9 (1.9%) were in the unspecified category. The mean age was 66 ± (SD) 13.60 years, women were older as compared to men (mean age 68.9 ± 13.12 years vs. 63.4 ± 13.53 years). Case fatality: at 28 days, 320 (70%) of 456 FES cases were still alive and 136 (29.8%) had died. Of the 320 surviving patients 38.5% had moderate to severe disability by the modified Rankin scale. Conclusions: The results of Mumbai stroke study, using uniform definitions and methodologies, show that the annual standardized incidence rates, stroke subtypes and case fatality rate are very similar to those reported from developed nations. To plan effective intervention and prevention strategies, standardized data in representative samples of regional populations are urgently needed.